Formal Ontology in Information Systems Proceedings of the Seventh International Conference (FOIS 2012) - Donnelly, Maureen (IOS Press, 2014)
This volume collects articles presented at the 7th edition of the International Conference on Formal Ontologies in Information Systems (FOIS 2012). This edition of this bi-annual conference was held in conjunction with with the 3rd edition of the International Conference on Biomedical Ontologies (ICBO 2012), in Graz, Austria.